Over-indebtedness of people living in socially excluded localities and social work with this target group - Urban, David (Journal of Nursing, Social Studies and Public Health, 2021)
Objectives: The objective is to reflect on the mechanisms of the origins of debts of Romani people in socially excluded areas and the options of solving this issue via social work. Theoretical base: Indebtedness of the population of the Czech Republic has increased over the past few years. A severe problem is the indebtedness of households in socially excluded areas, where the debt is caused by widely available access to unsecured loans or by the existence of loan-sharking in these areas. Methods: The research set consists of Romani people living in socially excluded areas and their social workers. In total, interviews were conducted with 13 communication partners (residents of socially excluded localities) and three social workers. Semi-structured interviews were used that were then analysed via the grounded theory method and contrasting. Results: It was found that the debts are in the order of tens, even several hundred thousand crowns, in some cases in the order of millions. It was revealed that the loans are multidimensional and demotivate Romani people from participating in the legal labour market. Social work implication: The results can be used by organisations working with people in debt to better evaluate and increase the quality of their services.
Keywords: Social Support; Social Isolation; Psychosocial Intervention; lidé; konzultanti; sociální izolace; dluhy; Social Problems; psychosociální intervence; Poverty; Consultants; Romové; sociální problémy; Roma; sociální práce; sociální opora; chudoba; Social Work; Humans